(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The information about the development of the Central Asian mysticism institutions in the XIV-XVI centuries, the artistic and constructive development of the architecture of the Khanaqah buildings, the khanaqahs of this period were built in the style of the magnificent architectural buildings in the form of symmetrical Composite dome-shaped structures and the construction of the "shock link", which There are also scientific summaries on protection, repair and use of objects of cultural norm.